2008
DOI: 10.1021/ol8022787
|View full text |Cite
|
Sign up to set email alerts
|

Base-Catalyzed Diels−Alder Reactions of 2H-Pyran-2,5-diones: A Mild Approach to Basiliolide B

Abstract: A new class of base-catalyzed Diels-Alder reactions of 2H-pyran-2,5-diones has been developed using catalytic amount of dicyclohexylmethylamine in tert-butyl alcohol. This method has been successfully employed for construction of the tricyclic core of basiliolide B at room temperature with good yields and exclusive endo selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 39 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…More interestingly, the basiliolides and transtaganolides contain an unprecedented 7‐methoxy‐4,5‐dihydro‐3 H ‐oxepin‐2‐one (C ring). Due to the unique structural features and the interesting biological activities, a considerable amount of efforts toward the biosynthesis and biomimetic synthesis of the basiliolide/transtaganolide family have been reported 48. As shown in Figure 1, an Ireland–Claisen rearrangement of prenyl 2‐pyrone 2 (isolated along with the transtaganolides by Massanet’s group) followed by an intramolecular 2‐pyrone Diels–Alder (DA) cycloaddition sequence has been proposed for the biosynthesis of the tricyclic core structure of transtaganolide E and F, which are the seco acid derivatives of transtaganolide D and C (basiliolide A1 and A2) 4.…”
Section: Methodsmentioning
confidence: 99%
“…More interestingly, the basiliolides and transtaganolides contain an unprecedented 7‐methoxy‐4,5‐dihydro‐3 H ‐oxepin‐2‐one (C ring). Due to the unique structural features and the interesting biological activities, a considerable amount of efforts toward the biosynthesis and biomimetic synthesis of the basiliolide/transtaganolide family have been reported 48. As shown in Figure 1, an Ireland–Claisen rearrangement of prenyl 2‐pyrone 2 (isolated along with the transtaganolides by Massanet’s group) followed by an intramolecular 2‐pyrone Diels–Alder (DA) cycloaddition sequence has been proposed for the biosynthesis of the tricyclic core structure of transtaganolide E and F, which are the seco acid derivatives of transtaganolide D and C (basiliolide A1 and A2) 4.…”
Section: Methodsmentioning
confidence: 99%
“…[4a] This reaction was first reported by Nakatanis group using a Brønsted base as the catalyst in 1995. [6] In the course of developing new methods for construction of the tricyclic core of basiliolide B, [7] we have found that 2H-pyran-2,5-diones can be used as a synthon of 5-hydroxy-2-pyrones for DA cycloadditions. [6] In the course of developing new methods for construction of the tricyclic core of basiliolide B, [7] we have found that 2H-pyran-2,5-diones can be used as a synthon of 5-hydroxy-2-pyrones for DA cycloadditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of this study, we have found that 2H-pyran-2,5-diones can be converted into 5-hydroxy-2-pyrones by treatment with catalytic amounts of base and undergo DA cycloaddition with acrylates at room temperature in a one-pot manner. [12] Here we disclose our full study of this new class of 2-pyrone DA cycloadditions, in which both the 2H-pyran-2,5-dione 1 and the 5-(tert-butyldimethylsilyloxy)-2-pyrone 2 can be utilized as synthons for 5-hydroxy-2-pyrones for DA cycloaddition (Scheme 2). …”
Section: Introductionmentioning
confidence: 99%